2015
DOI: 10.1515/amm-2015-0105
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Different Mechanical Milling Processes On Morphology And Microstructural Changes Of Nano And Micron Al-Powders

Abstract: In this research, effect of the various mechanical milling process on morphology and microstructural changes of nano and micron Al-powders was studied. The milling of Al-powders was performed by both high energy and low energy ball milling process. The influence of milling (pulverizing) energy on the structural changes of Al-powders was studied. Al-nanoparticles were agglomerated during the MA and its size was increased with increasing milling while micron Al-powder gets flattened shape during high energy ball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is observed that the powders are appeared to be very fine with irregular shape. Some fine powder is agglomerated with each other due to the cold welding taking place during milling are clearly visible in the micrographs [11]. In addition, the particle size analysis (PSA) is carrier out for p-type Bi 0.5 Sb 1.5 Te 3 powders, and shown in Fig.…”
Section: Methodsmentioning
confidence: 98%
“…It is observed that the powders are appeared to be very fine with irregular shape. Some fine powder is agglomerated with each other due to the cold welding taking place during milling are clearly visible in the micrographs [11]. In addition, the particle size analysis (PSA) is carrier out for p-type Bi 0.5 Sb 1.5 Te 3 powders, and shown in Fig.…”
Section: Methodsmentioning
confidence: 98%
“…The process lasted 12 h. Fig. 2 illustrates the ball-milling equipment for MNP synthesis and the difference in the low-and high-energy agglomeration surface morphological effects of the different ball milling processes [67]. The sizes and average crystallite concentrations of magnetite-based dispersions were also analyzed for different milling times for wet milling with argon gas [68].…”
Section: Ball-milling Methodsmentioning
confidence: 99%